2019
DOI: 10.1002/casp.2402
|View full text |Cite
|
Sign up to set email alerts
|

Challenge your stereotypes! Human Library and its impact on prejudice in Poland

Abstract: Human Library is a public event aimed at reducing stereotypes and prejudices, in the form of an interactive, contact‐based intervention. It employs the logic of a regular library yet with readers “borrowing” Living Books, which are real people representing various minority groups. Readers engage in 30‐min conversations, during which they can challenge their stereotypes and widen their scope of knowledge and understanding. This pre‐post intervention study examined the effectiveness of the Human Library (held in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…The MANOVA results showed that the human library was effective at reducing stigma and social distance, but did not affect knowledge acquisition. This study confirmed previous data showing that human library intervention promotes inclusion by reducing stigma and social distance [ 14 , 15 ]. However, the results of this study showed that participants in neither of the three groups demonstrated a significant improvement in the acquisition of knowledge about mental health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The MANOVA results showed that the human library was effective at reducing stigma and social distance, but did not affect knowledge acquisition. This study confirmed previous data showing that human library intervention promotes inclusion by reducing stigma and social distance [ 14 , 15 ]. However, the results of this study showed that participants in neither of the three groups demonstrated a significant improvement in the acquisition of knowledge about mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Their results suggested that prejudice towards Roma and LBGT people reduced significantly as a consequence of the human library intervention. Another study examined the effectiveness of a human library intervention at reducing social distance from Roma, Muslim, dark-skinned, and transgender people and homonegativity [ 15 ]. Groyecka et al (2019) found that participating in the human library significantly changed the preferred social distance from Muslims, but did not significantly change homonegativity.…”
Section: Introductionmentioning
confidence: 99%
“…In the second part of the study, we measured the participants' attitudes toward four nationalities (i.e., Hungarian, Italian, Mongolian, and Chinese), presented in a random order. We used the Bogardus social-distance scale [30,31], a measure commonly used to assess prejudice [32,33] that consists of three questions (i.e., whether participants would mind if a member of a given group was their co-worker, neighbor, and a part of their family). Participants responded to each question on a seven-point Likert scale (ranging from 1 = definitely would not mind to 7 = definitely would mind).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, their study indicated that the perceived prejudice of one's peers did not seem to fundamentally alter the effectiveness of the LL intervention. Groyecka, Witkowska, Wrobel, Klamut, and Skrodzka (2019) hypothesized in their study of a LL event in Wroclaw, Poland that talking to Books would affect social distance, homonegativity, and attitudes about diversity towards gays and lesbians, transgender individuals, Muslims, darkskinned people, and Roma. Online surveys following the event elicited responses from 87 Readers.…”
Section: Reader Attitudinal Changementioning
confidence: 99%